The Role of AI Chatbots In Enhancing Student Engagement and English Language Learning Outcomes at Raudhatul Athfal - Kurnia Akbar; Hasanah Hasanah; Ulfa Nafisa Rahmadani (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The rapid development of Artificial Intelligence (AI) has opened new opportunities in early childhood education, particularly in enhancing English language learning. This study aims to analyze the role of AI-based chatbots in increasing student engagement and learning outcomes in English for early childhood learners at RA Labschool IIQ Jakarta. Employing a mixed-methods design, the research integrates a quasi-experimental quantitative approach and descriptive qualitative techniques. Quantitative data were analyzed using Analysis of Covariance (ANCOVA) and post-hoc Least Significant Difference (LSD) tests, while qualitative data were examined through thematic analysis and triangulation. The results revealed that the experimental group using AI chatbots demonstrated significantly higher engagement and English learning achievements compared to the control groups, with F(2,26) = 65.14, p = 0.021, ƞ² = 0.95. Furthermore, qualitative findings indicated increased student motivation, interest, and interaction during learning activities. This study concludes that AI chatbots significantly contribute to fostering cognitive, emotional, and behavioral engagement, thereby improving learning outcomes. The findings imply that integrating AI-based technologies within early childhood curricula can enhance personalized, interactive, and adaptive learning experiences, while maintaining the crucial role of educators as facilitators.